EFFECT OF MATERIAL FLAWS ON THE MODAL PARAMETERS OF ISOTROPIC MATERIAL USING GROUND VIBRATION TESTING - Munir, A.; Khushnood, S.; Ahmed, N. (The Nucleus, 2013)
Modes are inherent properties of a structure, and are determined by the material properties (mass, damping, and stiffness), and boundary conditions of the structure. Experimental and numerical Ground vibration testing of the low carbon steel plate has been performed to study the changes in modal parameters (modal frequencies, mode shapes, mass, stiffness and damping) either by the load distribution or by material flaws like voids, cracks and porosity etc. Delicacies in experimental Ground vibration testing based on experimental experience are explained to define a methodology for precise experimental testing in order to avoid experimental uncertainties. The difference in numerical and experimental results is also discussed along with reasoning in order to estimate the accuracy of numerical and experimental results. The changes in natural frequencies and mode shapes have been studied for different cases. The cracks, holes and different masses have been induced in the plate and the shift of modal parameters was observed due to single flaw and the combination of flaws in order to estimate the effect of uncertainties in ground Vibration testing. After this research, it is concluded that due to material flaws the stiffness of the material changes, which ultimately affect the modal parameters. Due to change in modal parameters, Aeroelastic Analysis (Flutter speed) also changes, which might result as catastrophic failure of the structure.